2018
DOI: 10.3390/ma11060976
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Potassium Phosphate Compound for Immobilization of Radioactive Waste Containing Actinide and Rare Earth Elements

Abstract: The problem of effective immobilization of liquid radioactive waste (LRW) is key to the successful development of nuclear energy. The possibility of using the magnesium potassium phosphate (MKP) compound for LRW immobilization on the example of nitric acid solutions containing actinides and rare earth elements (REE), including high level waste (HLW) surrogate solution, is considered in the research work. Under the study of phase composition and structure of the MKP compounds that is obtained by the XRD and SEM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Like previous work [17] the experiments were carried out in a glove box (Pererabotka, Dzerzhinsk, Nizhny Novgorod region, Russia) at ambient atmospheric conditions and chemicals used in it were of no less than chemically pure grade.…”
Section: Chemicals and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Like previous work [17] the experiments were carried out in a glove box (Pererabotka, Dzerzhinsk, Nizhny Novgorod region, Russia) at ambient atmospheric conditions and chemicals used in it were of no less than chemically pure grade.…”
Section: Chemicals and Proceduresmentioning
confidence: 99%
“…Cubic samples of the MPP compound with dimensions of 2 cm × 2 cm × 2 cm were prepared as required by [26]. It was decided to keep the samples for at least 15 days at ambient atmospheric conditions in accordance with previous studies [17,25].…”
Section: Chemicals and Proceduresmentioning
confidence: 99%
“…At the set time, the samples were removed from the container, washed with double-distilled water (volume 100 mL), and combined with the leachate, and the content of 137 Cs in the combined solution was analyzed. The calculations of the differential leaching rate LR dif (g/(cm 2 •day)) and cumulative fraction leached F (%) of 137 Cs from compounds were made according to Equations (5) and (6).…”
Section: Synthesis and Study Of The Mpp Compoundsmentioning
confidence: 99%
“…Previously, in a number of literary sources [2][3][4][5][6][7][8][9][10][11][12][13], it was shown that the compound based on the magnesium potassium phosphate (MPP) matrix MgKPO 4 × 6H 2 O, which is formed at room temperature and is an analogue of the natural mineral K-struvite [14], is a promising material for immobilization of various LRW types, including HLW. A key task during HLW immobilization is to ensure binding of mobile cesium isotopes in the MPP compound.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the researchers found that the MPC can solidify radioactive waste within actinide and rare earth elements. The method of the MPC curing the LRW has the advantages of simple technology and high physical and chemical stability (Vinokurov et al, 2009(Vinokurov et al, , 2018b.…”
Section: Introductionmentioning
confidence: 99%